Through the eyes of science and art: a fourteenth-century winter breviary from Alcobaça scriptorium. Issue 2 (2nd July 2016) - Fernandes Barreira, Catarina; João Melo, Maria; Araújo, Rita; Casanova, Conceição
ABSTRACT: The collection of manuscripts from the monastery of Alcobaça is one of the most important in the Cistercian world. The scriptorium was active from the end of the twelfth to the sixteenth century, and during the end of the thirteenth and the beginning of the fourteenth centuries, transformations both in the materials used for colour and in style, namely historiated and filigreed initials, occurred. In this paper, through the study of a little-known manuscript, the winter Breviary Alc. 54, we will analyse these changes through a study of the pigments applied but also through the liturgy, which enables us to date the manuscript in the Alcobaça scriptorium with an original corpus from the earlier fourteenth century and two additions that were introduced during the second half of the fifteenth century. We argue that these transformations in style, materials and technique were catalysed by the entrance of "university" manuscripts into the abbey. In short, this research shows that the scriptorium was receptive to new ideas, which were absorbed and adapted to its own context. This manuscript provides examples of this: the use of silver in the illuminations, the updating of the palette, the French influence in the historiated initials, and the pen-flourished initials. While these changes were occurring, other Cistercian liturgical traditions and colour application technology stayed in use.